Auswertung der Online-Umfrage "Digitale Lehre" von H-Soz-Kult: "Digitale Lehre – Online-Befragung der Geschichtslehrenden an den Hochschulen im Sommersemester 2020" - Graf, Tobias P.; Hohls, Rüdiger; Pohlig, Matthias; Prinz, Claudia (2020)

Best of Enemies: Europeans in the Ottoman Elite - Graf, Tobias P. (History Today, 2018)

Case Studies in Early Modern Intelligence - Graf, Tobias P.; Backerra, Charlotte (Journal of Intelligence History, 2022)
This introduction to the special issue ‘Case Studies in Early Modern European Intelligence’ provides an overview of scholarship on the history of intelligence in the early modern period. Examining outstanding research contributions to the field, it highlights the potential of early modern European history to contribute to a refinement of the methodology and theory of intelligence history as a whole. In light of the contributions made by the articles collected in this special issue, we argue that intelligence history as a discipline will benefit from an increased dialogue between scholars working on different periods. We therefore invite historians of intelligence to study the early modern period and historians of the early modern period to study intelligence.<br
Keywords: Spionage; Geheimdienste; intelligence; Frühe Neuzeit; Europa

Cheating the Habsburgs and Their Subjects? Eighteenth-Century "Arabian Princes" in Central Europe and the Question of Fraud - Graf, Tobias P. (The Habsburg Mediterranean, 1500–1800, 2021)

Der Preis der Diplomatie. Die Abrechnungen der kaiserlichen Gesandten an der Hohen Pforte, 1580–1583 - Graf, Tobias P. (heiBOOKS, 2017)
Im Zuge eines material turn der historischen Forschung rücken die materiellen Aspekte frühneuzeitlicher Diplomatie zunehmend in den Fokus. Wie wurde Diplomatie finanziert? Welche Objekte wurden im Zuge des diplomatischen Geschenkverkehrs ausgetauscht? Welche Personenkreise wurden mit Gaben und gegebenenfalls Bestechungsgeldern bedacht? Die vorliegende Edition bisher unveröffentlichter Ausgabenabrechnung der kaiserlichen Gesandten an der Hohen Pforte Joachim von Sinzendorff und Friedrich Preiner aus dem Wiener Haus-, Hof- und Staatsarchiv unterstützt bei der Suche nach Antworten auf diese und vielfältige weitere Fragestellungen der neuen Diplomatiegeschichte. Ergänzt um ein umfangreiches Register und einen sachlichen Anmerkungsapparat, der besonderen Wert auf die Identifikation historischer Akteure sowie osmanischer Würdenträger und Fachbegriffe legt, eignet sich dieser Band sowohl für die historische Forschung als auch für die Verwendung in der Lehre.<br
Keywords: Diplomatie; Osmanisches Reich; Habsburgerreich; Finanzen; Geschenke; Spionage; Geheimdienste; Post- und Kurrierwesen; Frühe Neuzeit; 16. Jahrhundert

Encountering the Middle East in Early Modern Germany: A Prince of Palestine in Nuremberg, 1778–79 - Graf, Tobias (Encountering the Global in Early Modern Germany: Microhistories of Mobility, Materiality, and Belonging, 2025)
Between November 1778 and July 1779, the Free Imperial City of Nuremberg hosted the prince of Palestine Joseph Abaisi (Yūsuf Ḥubaysh). Contrary to what one might expect, we know about his visit not because of the reverence which this ostensibly eminent dignitary received from the city’s leaders, but because his conduct soon got him into so much trouble that the authorities felt it necessary to intervene to maintain peace and order. For Abaisi had overstayed his welcome, run into debt, and was accused of engaging in illegal gambling. The documentation produced by these proceedings allow a rare glimpse into the everyday activities and local interactions of an ‘Arabian prince’, a particular type of migrant to eighteenth-century Europe who, even though their numbers were modest, elicited much fascination and comment from contemporaries. At the same time, Abaisi’s case illuminates how Nuremberg as well as other German authorities more generally dealt with the presence of non-European foreigners. Abaisi’s example is not only a classic case of the ‘exceptional normal’, but also a useful reminder of how relatively normal the presence of seemingly exceptional foreigners was in the Holy Roman Empire, requiring German governments and administrators to not only acknowledge it, but to also find ways of dealing with the everyday consequences arising from it.<br
Keywords: Arabian princes; alms-collecting; migration; Maronites; Syria; Lebanon; Nuremberg; Germany; Holy Roman Empire; gambling; inns; legal conflict; debt

Europe’s Other(ed)s: The Americas, Africa, Asia, and Middle East in Early Modern History (ca. 1500–1800) - Martínez Bermejo, Saúl; Byrappa, Ramachandra; Graf, Tobias P.; Křížová, Markéta (The European Experience. A Multi-Perspective History of Modern Europe, 1500–2000, 2023)
Keywords: Europa; Entdeckungen; Alterität; Frühe Neuzeit

Exploring the Contact Zone. A Critical Assessment from the Perspective of Early Modern Euro-Ottoman History - Firges, Pascal; Graf, Tobias P. (Engaging Transculturality: Concepts, Key Terms, Case Studies, 2019)

Flugschrift über das Vordringen der Türken im Heiligen Land - Graf, Tobias P. (Pilgerspuren. Wege in den Himmel / Von Lüneburg an das Ende der Welt, 2020)

Interethnic Relations in Early Modern History (ca. 1500–1800) - Conrad, Benjamin; Graf, Tobias P.; Wille, Arndt (The European Experience. A Multi-Perspective History of Modern Europe, 1500–2000, 2023)
Keywords: Europa; Gesellschaft; Zusammenleben; Multiethnizität; Multireligiösität; Frühe Neuzeit

Introduction - Firges, Pascal; Graf, Tobias P. (Well-Connected Domains. Towards an Entangled Ottoman History, 2014)
Keywords: Osmanisches Reich; Europa; Verflechtungsgeschichte; connected history; Frühe Neuzeit

Keeping Secrets in Sixteenth-Century Istanbul - Graf, Tobias P. (2017)

Knowing the ‘hereditary enemy’: Austrian-Habsburg intelligence on the Ottoman Empire in the late sixteenth century - Graf, Tobias P. (Journal of Intelligence History, 2022)
Throughout the sixteenth century, the Ottoman Empire presented the most formidable challenge to the House of Habsburg’s predominance in Europe. This imperial rivalry and the military conflict which it generated made it vital that the Holy Roman Emperor and his advisors were kept informed about their powerful adversary to receive advance warning of impending attacks. For this reason, intelligence formed an important aspect of the day-to-day activities of the Aulic War Council, created in 1556 to coordinate the military defence of the Habsburg–Ottoman border, as well as the Austrian-Habsburgs’ resident ambassadors in Istanbul. Sources surviving in the Viennese archives provide valuable insights into the collection and dissemination of relevant information, as well as the organisation built by the Habsburg diplomatic presence in the Ottoman capital. In particular, this article examines ambassadorial expenditure accounts which provide insights into the financial aspects of Austrian-Habsburg intelligence in the period 1580–1583 and demonstrates that the business of intelligence was pursued by the Habsburgs in a more professional and orderly manner than historians usually acknowledge. Indeed, it was woven into the very fabric of the Aulic War Council as well as the Austrian-Habsburg diplomatic presence in Istanbul.<br
Keywords: Habsburgs; Austria; Ottoman Empire; intelligence organisation; intelligence funding; state; defence; war; diplomacy

Ladislaus Mörth. Ein ungewöhnlicher Renegat im Osmanischen Reich des späten 16. Jahrhunderts? - Graf, Tobias P. (Das osmanische Europa: Methoden und Perspektiven der Frühneuzeitforschung zu Südosteuropa, 2014)
Keywords: religiöse Konversion; Osmanisches Reich; Europa; Habsburgerreich; Militärgrenze; Istanbul; Spionage

Migration in Early Modern History (ca. 1500–1800) - Behrisch, Lars; Graf, Tobias P.; Horn, Ildikó; Rodríguez García, Margarita Eva (The European Experience. A Multi-Perspective History of Modern Europe, 1500–2000, 2023)
Keywords: MIgration; Frühe Neuzeit; Europa

Of Half-Lives and Double-Lives: "Renegades" in the Ottoman Empire and Their Pre-Conversion Ties in the Late Sixteenth and Early Seventeenth Centuries - Graf, Tobias P. (Well-Connected Domains: Towards an Entangled Ottoman History, 2014)
Keywords: religiöse Konversion; Osmanisches Reich; Europa; Frühe Neuzeit; trans-imperial subjects

Stopping an Ottoman Spy in Late Sixteenth-Century Istanbul. David Ungnad, Markus Penckner, and Austrian-Habsburg Intelligence in the Ottoman Capital - Graf, Tobias P. (Rethinking Europe. War and Peace in the Early Modern German Lands, 2019)

The Sultan’s Renegades: Christian-European Converts to Islam and the Making of the Ottoman Elite, 1575–1610 - Graf, Tobias P. (Oxford University Press, 2017)
he figure of the renegade - a European Christian or Jew who had converted to Islam and was now serving the Ottoman sultan - is omnipresent in all genres produced by those early modern Christian Europeans who wrote about the Ottoman Empire. As few contemporaries failed to remark, converts were disproportionately represented among those who governed, administered, and fought for the sultan. Unsurprisingly, therefore, renegades have attracted considerable attention from historians of Europe as well as students of European literature. Until very recently, however, Ottomanists have been surprisingly silent on the presence of Christian-European converts in the Ottoman military-administrative elite. The Sultan's Renegades inserts these 'foreign' converts into the context of Ottoman elite life to reorient the discussion of these individuals away from the present focus on their exceptionality, towards a qualified appreciation of their place in the Ottoman imperial enterprise and the Empire's relations with its neighbours in Christian Europe. Drawing heavily on Central European sources, this study highlights the deep political, religious, and cultural entanglements between the Ottoman Empire and Christian Europe beyond the Mediterranean Basin as the 'shared world' par excellence. The existence of such trans-imperial subjects is not only symptomatic of the Empire's ability to attract and integrate people of a great diversity of backgrounds, it also illustrates the extent to which the Ottomans participated in processes of religious polarization usually considered typical of Christian Europe in this period. Nevertheless, Christian Europeans remained ambivalent about those they dismissed as apostates and traitors, frequently relying on them for support in the pursuit of familial and political interests.<br
Keywords: religiöse Konversion; Osmanisches Reich; Europa; Renegaten; Elitenformation; trans-imperial subjects; Frühe Neuzeit; 16. Jahrhundert; 17. Jahrhundert

Trans-Imperial Nobility: The Case of Carlo Cigala (1556–1631) - Graf, Tobias P. (Conversion and Islam in the Early Modern Mediterranean: The Lure of the Other, 2017)
Keywords: religiöse Konversion; Osmanisches Reich; Europa; Italien; Adel; trans-imperial subjects; Frühe Neuzeit

Von richtigen Papieren und legitimen Anliegen. Beobachtungen zur verwaltungssprachlichen Konstruktion ‚arabischer Prinzen‘ und zum Umgang der Nürnberger Obrigkeit mit diesem besonderen Typus ausländischer Bittsteller im 18. Jahrhundert - Graf, Tobias P. (Die Sprachen der Frühen Neuzeit: Europäische und globale Perspektive, 2024)
Keywords: Almosensammler; Ostchristen; Maroniten; Verwaltung; Verwaltungssprache; Nürnberg; Frühe Neuzeit

Well-Connected Domains: Towards an Entangled Ottoman History - Firges, Pascal; Graf, Tobias P.; Roth, Christian; Tulasoğlu, Gülay (Brill, 2014)
Keywords: Osmanisches Reich; Europa; Verflechtungsgeschichte; connected history; Frühe Neuzeit; 19. Jahrhundert

Wie funktionierte Alterssicherung in der Frühen Neuzeit? - Graf, Tobias P. (2022)
Keywords: Alterssicherung; Europa; Frühe Neuzeit